(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Abstract: This thesis explores the concept of translator style, examining its definition, types, and importance in translation studies. It analyzes the perspectives of scholars such as Malmkjaer, focusing on source text patterns; Boase-Beier, emphasizing cognitive and creative translation; Baker, highlighting the translator's linguistic fingerprint; and Munday, linking stylistic choices to broader contexts. The study also evaluates the practical implications of translator style for quality control, audience adaptation, and the creative aspects of translation.